Physical Activity in Patients with IBD - Challenge, Opportunity, or Both? - Aab, Arkadiusz; Zarańska, Julia; Kędra, Kamila; Michalik, Izabela; Bielak, Maciej (Journal of Education, Health and Sport, 2023)
Introduction: Inflammatory bowel diseases (IBD) are a global public health problem, and their incidence is continuously increasing. IBD is characterized by a relapsing nature and is associated with symptoms such as abdominal pain, diarrhoea, malabsorption, and nutritional deficiencies. Patients affected by this disease are typically young individuals, and physical activity plays a significant role in this age group. Understanding the role of exercise and sports activities in individuals with IBD can help consider potential therapeutic interventions for these patients. Objective: The aim of this study is to summarize the knowledge regarding the role of physical activity in patients with IBD. Materials and methods: A literature review was conducted using the PubMed and Google Scholar databases, using the following keywords: IBD, physical activity, stress and fatigue in individuals with IBD, anxiety in patients with IBD. State of knowledge: The role of physical activity in promoting health and preventing various diseases is well-established. However, there is limited research on the association between exercise and IBD. Conclusions: Physical activity, by reducing fatigue and stress, has a positive impact on the functioning of patients with IBD. There are reports suggesting a reduction in gastroenterological symptoms in patients after engaging in exercise. With appropriate control of the underlying disease using pharmacological and other recommended methods, participating in sports activities does not pose a barrier for patients. Physicians should encourage patients to engage in exercise with tailored intensity due to its beneficial effects on various aspects of life for individuals with IBD. Further research is necessary to explore this topic more extensively.